Leslie Alcock - Driscoll, Stephen T (Proceedings of the Society of Antiquaries of Scotland, 2007)
Professor Leslie Alcock will probably be most widely remembered for his book Arthur’s Britain – which made a lasting impact on the scholarly community and was hugely popular – and for his excavations at the hillfort of South Cadbury-Camelot, Somerset, which attracted world-wide media attention.